The role of teachers in curriculum development character-based Arabic learning in Madrasah Ibtidaiyah - Rusdy Iskandar; Andi Prastowo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to describe the role of teachers in developing a character-based Arabic curriculum, examine how curriculum development enhances the implementation of character education, identify the character values integrated into the Arabic curriculum, and analyze the supporting and inhibiting factors in its development. This research employs a qualitative approach with a phenomenological method. The study was conducted at MIM Gading 1 Klaten, with data collected through observation, interviews, and documentation. The findings reveal that Arabic language teachers are crucial in designing syllabi and lesson plans (Learning Implementation Plans) based on character education principles integrated into Arabic language instruction. Teachers function as implementers, adapters, developers, and researchers. Additionally, they serve as motivators, organizers, facilitators, and student role models. A character-based Arabic curriculum is developed by embedding character values into Arabic language subjects. The key values incorporated include religiosity, obedience, discipline, communication skills, self-confidence, curiosity, empathy, and responsibility.